Identification of Lipase-Producing Thermophilic Bacteria Isolated From Hot Springs in Malaysia - Kamaruzaman, Azura Liana (2008)
Lipase-producing thermophilic microorganisms were successfully isolated from water samples collected from six hot springs in the west coast of Peninsular Malaysia and were identified up to species level. Five hundred and forty-four microbial colonies were qualitatively screened using Rhodamine B-olive oil agar plate method and sixty-six were found to be positive as bacterial lipase producers after they formed orange fluorescent colour around the colonies when irradiated with UV light. Lipolytic activities were assayed using titrimetric method with olive oil emulsion as substrate. Comparative analysis among the positive bacterial lipase producers indicated that isolate ST 7 had the highest lipolytic activity of 4.58 U/ml, followed by isolate ST 6 with an activity of 3.51 U/ml. Eighteen isolates that showed high lipolytic activity were further examined for thermostability. Thermostability was determined by incubation of the crude lipase at temperature ranging from 40 to 80°C for 30 minutes. It was found that isolates ST 7 and ST 8 produced the most thermostable lipase, which retained 86.70% and 87.52% of the original activity after incubation at temperature 80°C for 30 minutes, respectively. Eighteen lipase-producing thermophilic bacteria were further characterized and identified using morphological characteristics, Biolog Microlog® Bacterial Identification System and conventional biochemical tests. Strains KW 6, KW 7, ST 1, ST 6 and ST 10 were identified as CDC Group IVc-2 (Alcaligenes-like) or Ralstonia paucula. Strains KW 8, KW 10 and DT 17 were identified as Burkholderia cocovenenans, B. glumae and Photobacterium logei, respectively. Biolog identified strains ST 7, ST 8, SY 7, KW 1, KW 9, KW 12 and TBN 3 were belonging to genus Bacilli and strains SY 9, DT 9 and DT 12 as Staphylococcus species. Four strains of the Bacillus genus with the highest thermostability, ST 7, ST 8, SY 7 and KW 12 were chosen for further identification using 16S rRNA gene sequence analysis. The protocol of DNA extraction method applied in this study was Qiagen DNeasy Tissue Kit. Based on the quantification of extracted DNA and estimation of the purity by UV spectrophotometer, the Qiagen DNeasy Tissue Kit produced a high DNA yield of all samples. The primer pair used for specific-PCR generated the same expected PCR product for all the strains with molecular weight of 1500 bp. Sequences were determined using an automated sequencer; which was aligned with reference sequences of the closest related organisms in NCBI database. Based on 16S rRNA gene sequencing, the highest sequence similarity was found between strain ST 8 and Bacillus subtilis gene for 16S rRNA partial sequence (AB110598 with 100% similarity between nucleotides 1- 1532). Strains KW 12 and ST 7 were also showed a high sequence similarity at 99.0%; comparable to those of Anoxybacillus kamchatkensis 16S rRNA gene partial (accession number: AF510985) and Anoxybacillus flavithermus isolate AB05 16S rRNA gene partial sequence (accession number: AF001964), respectively. Strain SY 7 displayed 98.0% sequence similarity to Bacillus cereus strain J-1 16S rRNA gene partial sequence (accession number: AY305275). The 16S rRNA gene sequences for ST 8, ST 7, KW 12 and SY 7 have been deposited into Genbank Data Library and assigned the accession number DQ401073, DQ193516, DQ401072 and DQ401074, respectively.